Bourdieu in der Germanistik - Schmidt, Karsten; Stiemer, Haimo (De Gruyter, 2022)
This volume brings into dialogue current research interests in literary studies and linguistics that work with Pierre Bourdieu's concepts and theory. In light of the twentieth anniversary of the death of the French sociologist (2022), it thus, firstly, carries out a survey of previous research and, secondly, stakes out the future potential of German studies oriented toward Bourdieu.